Influence analysis of room division employee job training on service quality, guest satisfaction and returning interest at PT. Baleka Selaras Mandiri - Paramita, Anak Agung Yunita Devi; Zuraida, Lukia; Damayanti, Titien (International research journal of management, IT and social sciences, 2024)
This research aims to analyze the effect of work training for room division employees at PT. Baleka Selaras Mandiri regarding service quality, guest satisfaction and interest in returning. This research is a quantitative research type. Data collection was carried out through distributing questionnaires at three PT properties. Baleka Selaras Mandiri namely Baleka Resort & Spa, Villa Tukad Alit Kerobokan and The Tukad Villa Seminyak. The total number of respondents in this study was 100 respondents. The collected data was then tested for reliability and validity, and the results showed that the data was reliable and valid so that it could be used in further analysis. Hypothesis testing was carried out by the Manova test and the results obtained were that the Sig. < 0.05. These results show that work training has a positive and significant effect on service quality, work training has a positive and significant effect on guest satisfaction, and work training has a positive and significant effect on interest in returning.